Basic research and clinical exploration of cold atmospheric plasma for skin wounds - Miaomiao Li; Jing Gao; Liyun Wang; Jia Liu; Chuyu Fu; Xingyu Yang; Shengquan Zhang; Xinwei Li; Shengyong Luo; Chunjun Yang (Wiley, 2023)
Abstract Skin wounds, such as burns, diabetic foot ulcers, pressure sores, and wounds formed after laser or surgical treatment, comprise a very high proportion of dermatological disorders. Wounds are treated in a variety of ways; however, some wounds are greatly resistant, resulting in delayed healing and an urgent need to introduce new alternatives. Our previous studies have shown that cold atmospheric plasma (CAP) has antibacterial activity and promotes cell proliferation, differentiation, and migration in vitro. To further advance the role of CAP in wound healing, we evaluated the safety and efficacy of CAP in vitro by irradiation of common refractory bacteria on the skin, irradiation of normal skin of rats and observing reactions, treatment of scald wounds in rats, and treating clinically common acute wounds. Our findings revealed that CAP can eliminate refractory skin bacteria in vitro; CAP positively affected wound healing in a rat scalding wound model; and direct CAP irradiation of low intensity and short duration did not lead to skin erythema or edema. CAP promises to be a new, economical, and safe means of wound treatment.